The Effect of Entrepreneurial Competencies on Business Success : A Study with Special Reference to SMEs at Kanchipuram District - Ramanathan, V.; Sonia, C. (AMC Indian Journal of Entrepreneurship, 2018)
Entrepreneurial venture has become worthwhile business occupation among new generation entrepreneurs in India. The impact of globalization, free market economy, and liberalized zones of manufacturing have paved the way for establishment of new start-ups under the category of Small and Medium Enterprises (SMEs). The proliferation of SMEs in manufacturing and services established the landmark of competitive business environment. However, at the same time successful business promotion and growth of SMEs rely on the competencies of entrepreneurs. This research paper attempts to view the influence of entrepreneurial competencies on the business success of selected SMEs in manufacturing and services sectors. 351 entrepreneurs were surveyed for this and aÂ structured questionnaire was used. A structural model was developed to test the effect of entrepreneurial competency on their business success through AMOS 20.